Prevalence, variability, and predictors of sinus surgery in pediatric patients with cystic fibrosis. Issue 12 (14th October 2021) - Virgin, Frank W.; Thurm, Cary; Sanders, Don B.; Freeman, Alvin J.; Cogen, Jonathan; Gamel, Breck; Sawicki, Greg; Fink, Aliza K.
Abstract: Introduction: Chronic rhinosinusitis is common among individuals with cystic fibrosis (CF) and has an impact on quality of life. Sinus surgery is a treatment option, but minimal literature exists regarding prevalence and indications. Methods: Using the linked CF Foundation Patient Registry (CFFPR) – Pediatric Health Information Systems (PHIS) database, we investigated variability in receipt of surgery, predictors of surgery, and time to first surgery. We included individuals less than 18 receiving care between 2006 and 2015 at a CF Foundation care program that is also a PHIS‐participating‐hospital. We used logistic regression to examine predictors of receipt of surgery and a Kaplan–Meier curve to examine time to first surgery among those born 2005–2007. Results: There were 11, 545 children and adolescents and 2156 (18.7%) received at least one surgery. Variation in number of surgeries was observed across hospitals (median: 63 [IQR, 33–110]). There was an inconsistent pattern between receipt of surgery and markers of disease severity; those receiving surgery having increased odds of treatment use and pulmonary exacerbations and decreased odds of lower lung function and body mass index. Among the cohort of young children, 159 (14%) had at least one surgery with a median age at first surgery of 5.6 (IQR, 3.9–7.0). Conclusions: The use of sinus surgery is frequent, but variable, among children and adolescents. Clinical factors are associated with receipt of surgery, but further understanding is needed on other factors that impact variability in use. Our study indicates the need for additional evaluation of the management of CF‐related CRS and indications for surgery.